2012
DOI: 10.1100/2012/169724
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Driving Factors of Grassland Degradation: A Case Study in Xilin River Basin, Inner Mongolia

Abstract: Current literature suggests that grassland degradation occurs in areas with poor soil conditions or noticeable environmental changes and is often a result of overgrazing or human disturbances. However, these views are questioned in our analyses. Based on the analysis of satellite vegetation maps from 1984, 1998, and 2004 for the Xilin River Basin, Inner Mongolia, China, and binary logistic regression (BLR) analysis, we observe the following: (1) grassland degradation is positively correlated with the growth de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
(61 reference statements)
1
24
0
1
Order By: Relevance
“…While constructing more road networks expanded the domain of human activities, it also might lead to more damage to the grassland vegetation due to the easier access to vegetated areas. The side impact on vegetation due to road networks on grasslands has been documented by a few studies investigated in Inner Mongolia and Mongolia [18,57]. The paper [57] also analyzed a few reasons, including the hardness of the top layer and soil erosion, for the damage imposed by road tracks on grasslands.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While constructing more road networks expanded the domain of human activities, it also might lead to more damage to the grassland vegetation due to the easier access to vegetated areas. The side impact on vegetation due to road networks on grasslands has been documented by a few studies investigated in Inner Mongolia and Mongolia [18,57]. The paper [57] also analyzed a few reasons, including the hardness of the top layer and soil erosion, for the damage imposed by road tracks on grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the average neighborhood characteristic for DD developed from RR and NS showed a negligible change to window size when it was beyond seven units. Considering this result, as well as the previous study on vegetation density interpolation [18], d was set to seven (equivalent to a window with 1.75 km in width).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations